Punta GuaPa an integrative urban generator in Guadalupe and Pasig River - Manuel, Rachelle Lea C.
As we aim to connect Pasig River to the urban city of Metro Manila to help make the river transport system work and help ease the traffic congestion on land, promoting the river tourism is a must. Though Pasig River has a strong tourist potential, challenges still occur to make it possible. For a strong integrating transportation node, Guadalupe in Makati is chosen. The city is currently disconnected from the waterfront, resulting to an unattractive layout for recreational and cultural activities. The cloverleaf parks are also underutilized and this gives an opportunity for integration management. Moreover, people have already lost their affinity to the river, and for this, an urban generator is designed. It consists of museum, library, office, pedestrian bridge, pedestrian tunnel, and ferry terminal. All functions were derived according to the need of the site to encourage and bring the river back to the people's system.